2021
DOI: 10.1038/s41467-021-22132-0
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy protects macaques against advanced Marburg virus disease

Abstract: Monoclonal antibodies (mAbs) and remdesivir, a small-molecule antiviral, are promising monotherapies for many viruses, including members of the genera Marburgvirus and Ebolavirus (family Filoviridae), and more recently, SARS-CoV-2. One of the major challenges of acute viral infections is the treatment of advanced disease. Thus, extending the window of therapeutic intervention is critical. Here, we explore the benefit of combination therapy with a mAb and remdesivir in a non-human primate model of Marburg virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 50 publications
0
45
0
2
Order By: Relevance
“…While higher doses of MBP134 administered via IV have already demonstrated complete protection (Bornholdt et al, 2019), the 5 mg/kg IM dosing of MBP431 tested here represents a potentially realistic single dose IM regimen for an average weight human. It remains to be determined if lower doses of MBP431 tested here in combination with small molecule-based treatments like Remdesivir could amplify protective efficacy via augmented biodistribution in more severe cases as was observed in recent combination studies for the treatment of marburgvirus infection (Cross et al, 2021). Future experiments will also focus on the prophylactic utility of MBP431 when administered IM in NHP models of ebolavirus infection.…”
Section: Discussionmentioning
confidence: 91%
“…While higher doses of MBP134 administered via IV have already demonstrated complete protection (Bornholdt et al, 2019), the 5 mg/kg IM dosing of MBP431 tested here represents a potentially realistic single dose IM regimen for an average weight human. It remains to be determined if lower doses of MBP431 tested here in combination with small molecule-based treatments like Remdesivir could amplify protective efficacy via augmented biodistribution in more severe cases as was observed in recent combination studies for the treatment of marburgvirus infection (Cross et al, 2021). Future experiments will also focus on the prophylactic utility of MBP431 when administered IM in NHP models of ebolavirus infection.…”
Section: Discussionmentioning
confidence: 91%
“…Remdesivir administered once daily with a 10-mg/kg loading dose followed by a 5-mg/kg maintenance dose for 12 days provided an 83% survival outcome [ 36 ]. An additional study reported by a different research group found that remdesivir administration using the same 10/5 mg/kg for 12 days initiated 5 days postinfection provided 80% survival using a MARV challenge model using rhesus macaques [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…A combination therapy study in patients has not been conducted to date, and the Ebola outbreak has since subsided, suggesting that an NHP bridging study might be useful. Interestingly, Cross and colleagues recently reported that combination therapy consisting of remdesivir and a human antibody targeting MARV achieved 80% protection against advanced disease in a MARV challenge model using rhesus macaques while remdesivir only or mAb only treatment yielded no survivors [ 37 ]. While two of the antibody therapies in the PALM trial showed the greatest clinical benefit for treatment of ZEBOV infections, both are specific for ZEBOV with no activity against other filoviruses.…”
Section: Resultsmentioning
confidence: 99%
“…Remdesivir exhibits promising pharmacological properties in vitro, including against SARS‐CoV, MERS‐CoV, EBOV, and SARS‐CoV‐2 with EC 50 values of 0.069, 0.090, 0.012, and 0.77 μM, respectively 64 . In animal models, remdesivir has been demonstrated to protect monkeys from infection by the respiratory syncytial virus (RSV), 65 Marburg virus, 66 MERS‐CoV, 67 EBOV, 68 and SARS‐CoV‐2 69 . Combination of remdesivir with other agents, such as itraconazole, simeprevir, or methylprednisolone, produces a significant synergistic effect compared with remdesivir alone, both in vitro and in animal models 70–72 .…”
Section: Broad‐spectrum Prodrugs Targeting Sars‐cov‐2 Rdrpmentioning
confidence: 99%